Birds and habitats recorded in the lower Mai Valley Important Bird and Biodiversity Area - Inskipp, Carol; Acharya, Sanjib; Giri, Tikaram (Nepalese Journal of Zoology, 2022)
A bird survey was carried out in the lower Mai Valley Forests (MVF) Important Bird and Biodiversity Area (IBA) in far eastern Nepal, between 180 m and 2200 m from 01 to 10 March 2022. An assessment was also made of the environmental conditions of forest and river habitats, and type and extent of agriculture. A comparison was made with a March 1981 visit. Observations were noted during a ten-day trek from Ilam (1205 m) up to Hangetham (2200 m) and down to Sukhani (180 m). The large number of 256 bird species was recorded, including one globally threatened and five globally near-threatened species, five restricted-range species, 20 nationally threatened and eight nationally near-threatened species. One new species for Nepal, black-breasted thrush Turdus dissimilis and three rare Nepal species not found in the IBA for at least 20 years, were also recorded. Extensive intact areas of semi-evergreen subtropical and lower temperate mixed broadleaved forests valuable for birds still remain. Tropical forests have been fragmented and mainly replaced by tea and rubber plantations, and also by the spread of agriculture. However, Sukhani still comprises a substantial semi-evergreen broadleaved forest important for birds, although it is highly threatened. Hunting is probably a significant threat to bird species in MVF. Despite loss and degradation of some forests, especially in the tropical zone, MVF still qualify as an IBA. The Mai Khola habitat has been severely damaged by the Mai Khola Hydroelectric Project, which became operational in 2015, resulting in serious declines in river birds. MVF remain outside the existing protected area network. Including MVF in Nepal’s protected area system would ensure conservation of the species-rich semi-evergreen mixed broadleaved tropical and subtropical forests that are currently an important omission. Further bird surveys are recommended at all elevations and in tropical and subtropical forests that have so far not been covered.